2009
DOI: 10.1902/jop.2009.080521
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor‐Alpha Levels After Surgical Anti‐Infective Mechanical Therapy for Peri‐Implantitis: A 12‐Month Follow‐Up

Abstract: The anti-infective mechanical therapy reduced the crevicular levels of TNF-alpha in sites affected by peri-implantitis over a period of 12 months, and this phenomenon was associated with improvements in clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 32 publications
0
46
0
1
Order By: Relevance
“…In line with previous findings, there were no differences with regards to IL-6, IL-8, IL-10 (Severino et al 2011), whereas the levels of IL-1β were significantly higher at peri-implantitis, compared to mucositis sites. Further studies also showed that peri-implantitis treatment reduced the PICF levels of IL-1β (Bassetti et al 2013) and TNF-α (de Mendonca et al 2009;Duarte et al 2009a). Studies have also demonstrated that single nucleotide polymorphisms (SNP) in the IL-1 gene may hold an increased risk for the development of peri-implantitis, particularly when combined with smoking (Andreiotelli et al 2008;Bormann et al 2010).…”
mentioning
confidence: 94%
“…In line with previous findings, there were no differences with regards to IL-6, IL-8, IL-10 (Severino et al 2011), whereas the levels of IL-1β were significantly higher at peri-implantitis, compared to mucositis sites. Further studies also showed that peri-implantitis treatment reduced the PICF levels of IL-1β (Bassetti et al 2013) and TNF-α (de Mendonca et al 2009;Duarte et al 2009a). Studies have also demonstrated that single nucleotide polymorphisms (SNP) in the IL-1 gene may hold an increased risk for the development of peri-implantitis, particularly when combined with smoking (Andreiotelli et al 2008;Bormann et al 2010).…”
mentioning
confidence: 94%
“…Mechanical peri-implant therapy leads to reduced TNF-α levels in the crevicular fluid associated with improved clinical parameters [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic species stimulate proinflammatory cytokines, such as interleukin (IL)-1b, IL-6, and tumor necrosis factor (TNF)-a, which coordinate many aspects of the local inflammatory response. 35 TNF-a subsequently induces more adhesion molecules, proinflammatory cytokines, and chemokines as well as induces osteoclast function resulting in bone loss. Peri-implant crevicular fluid TNF-a may be an indicator for peri-implant inflammation and may precede indicators such as BOP increased probing depth (PD), providing for an earlier diagnosis.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Peri-implant crevicular fluid TNF-a may be an indicator for peri-implant inflammation and may precede indicators such as BOP increased probing depth (PD), providing for an earlier diagnosis. 35 There is potential for genetic alterations of any of the above factors to influence periimplantitis. IL-1 is a group of 11 cytokines that are involved in the regulation of immune and inflammatory responses.…”
Section: Genetic Factorsmentioning
confidence: 99%